The Effect of pH and TDS on the Corrosion Rate of Carbon Steel - Al-Hasen, Nuha H. (Basrah Journal for Engineering Sciences, 2008)
The aim of this paper is to reduce the corrosion rate by controlling the pH value, the polarization technique was used in this research in acidic, neutral and basic solutions. The corrosion rate was studied for carbon steel in filtered water, raw water and de-mineralized water under static condition at room temperature and 1 atm. Also, the effect of total dissolved solid (calcium, magnesium and sodium) on the corrosion rates was studies.